Linking Research and Consumers through Adult Education Programmes for the Advancement of Small-scale Food Industries in Malaysia - Muhamad, Mazanah; Tajuddin Shah, Raja Ahmad; Hamzah, Azimi (Universiti Putra Malaysia Press, 1995)
This paper describes and highlights features of an adult education programme implemented by the Food Technology Division of the Malaysian Agriculture Research and Development Institute (MARDI) to promote the food industry in Malaysia. A study on the programme was carried out using in depth interviews, participant observation and content analysis of documented data. The programme encompasses three basic components generating technology appropriate for small food industries, interfacing between innovators and consumers, and coaching learners to ensure the enterprise becomes successful and sustainable. The discussions focus on the efforts by the division to integrate its research and extension activities. Examination of the programme reveals that it integrates research and extension as suggested by Bennetts (1989) interdependency model. Strengths and weaknesses of this approach are discussed in the paper.